2021
DOI: 10.3390/su13010421
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Scale of Food Waste in Hotel Food Services—A Case Study

Abstract: The problem of food waste in food services, which is global and essentially affects the entire world, is a major challenge for the hospitality industry. At the same time, it should be noted that this problem has not been sufficiently studied, which makes it difficult to reduce it effectively. The study was carried out in four hotels in late 2019 and early 2020. In order to determine the scale of food waste, the diary method was used, which consists of systematically recording, for seven days, in forms prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…The awareness regarding waste seems to be improving, but the food sector still wastes a lot of the meals produced. In the study by Tomaszewska et al [37], which created and analyzed a waste scale for the hotel sector, the authors reinforced that employees need to be more trained in food handling and that it is of paramount importance to make consumers aware of the negative impact generated by food waste. It is important to note that the mandatory score in the three sections was based on our previous study [13], which, through a systematic review, reinforces the importance that for the restaurant to be sustainable, it needs to have activities that cover the three sustainability indicators.…”
Section: Discussionmentioning
confidence: 99%
“…The awareness regarding waste seems to be improving, but the food sector still wastes a lot of the meals produced. In the study by Tomaszewska et al [37], which created and analyzed a waste scale for the hotel sector, the authors reinforced that employees need to be more trained in food handling and that it is of paramount importance to make consumers aware of the negative impact generated by food waste. It is important to note that the mandatory score in the three sections was based on our previous study [13], which, through a systematic review, reinforces the importance that for the restaurant to be sustainable, it needs to have activities that cover the three sustainability indicators.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be stated that the fact that this reason was included in the created model proves its importance. The low position in the model may be influenced by the fact that environmental aspects are not always considered in the surveyed countries, both by consumers and food-producing plants [4,62].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of all-inclusive hotels, they prefer to serve guests using a buffet service style that generates a high amount of FLW in comparison to other service types [4]. For example, Tomaszewska [25] found that hotel guests were not able to consume all the breakfast buffet's items; on a daily basis, the breakfast buffet had an average of 3.6 kg of unconsumed food for each in-house guest. While the hotel business contributes to food and energy consumption, it is hampered by the cost challenges associated with bulk food processing [41].…”
Section: Flw In the Hotel Industrymentioning
confidence: 99%
“…Furthermore, Tekin and Ilyasov [23] confirmed that guests in all-inclusive hotel resorts often waste more food and beverages than others because they will not pay for extra consumption; moreover, all-inclusive hotels often serve their guests using an open buffet. Addressing the issue of tackling food waste in all-inclusive resort hotels is a complicated issue [24,25]. Food waste is frequently regarded as an unfortunate consequence of the all-inclusive philosophy, where food is prepared and served on a near-constant basis at serving outlets located throughout the hotel [24].…”
Section: Introductionmentioning
confidence: 99%